The Human Use of the Human Face: The Photographic Self-Portrait in the Age of the Selfie - Donnachie, Karen Ann (Curtin University, 2015)
Karen Ann Donnachie's research explores the phenomenon of the selfie as a vehicle for the mass projection of self and the effect it has on contemporary notions of identity, society and photography. During her practice-led research, Donnachie created electronic, algorithmic and Internet artworks including self-made and self-programmed ‘selfie’ cameras. This thesis maps the complex genre of the selfie between performance, narcissism, social tic, intrinsic desire for self-projection and a quest for authenticity and human connection.